ANALISIS TINGKAT KEBUGARAN JASMANI SISWA SEKOLAH DASAR NEGERI 1 TAMANREJO KECAMATAN SUKOREJO KABUPATEN KENDAL - Yoga Nanda Pratama; Buyung Kusumawardhana; Utvi Hinda Zhannisa (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2025)
Physical education is a compulsory subject in schools across all educational levels, including elementary, junior high, high school, and vocational institutions. The goal of physical education is to enhance the physical, mental, social, and emotional fitness of individuals through various forms of physical activity. Physical fitness is defined as a person's ability to carry out daily activities effectively and without excessive fatigue, though fitness levels vary among individuals based on their engagement in physical exercise. This study aims to assess the physical fitness of students at SD Negeri 1 Tamanrejo, Kendal Regency. The research uses a descriptive method involving tests and measurements. Descriptive research is employed to describe specific phenomena or events related to students' physical fitness, particularly VO2Max of students at SD Negeri 1 tamanrejo, Kendal Regency. Physical fitness was measured using the MFT (Multistage Fitness Test) and analyzed through normality and t-tests. The results showed variations between pretest and post-test scores, with the average pretest score for boys being 29.31 and post-test score 32.45, while the average pretest score for girls was 26.56 and post-test score 31.0. This indicates that the 22 students from SD Negeri I tamanrejo experienced an increase in physical fitness, with boys showing a 10.70% improvement and girls a 16.75% improvement.